High-sensitivity, protein-independent detection of dsDNA sequences - Jiaqi Yan; Rajendra Bhadane; Wentao Xu; Meixin Ran; Xiaochao Ma; Yuanqiang Li; Kevin Jahnke; Xiaodong Ma; Outi M. H. Salo-Ahen; Mauri A. Kostiainen; David A. Weitz; Hongbo Zhang (Proceedings of the National Academy of Sciences, 2026)
Current methodologies for detecting the sequence of double-stranded DNA (dsDNA) require amplifying and denaturing the target into single-stranded DNA (ssDNA) to enable sequence detection through Watson–Crick base pairing. However, these approaches are limited by the risks of nonspecific amplification, reliance on complex, temperature-sensitive protein enzymes, and harsh reaction conditions, such as in strong base or acidic environments. Here, we introduce a dsDNA detection platform that integrates a peptide nucleic acid (PNA) as the dsDNA denaturation agent, with multicomponent deoxyribozyme as the ssDNA detection tool, in a droplet-based system. This protein- and amplification-free method offers single-nucleotide resolution, detects down to a single dsDNA molecule, and delivers results within 1 h at room temperature. This work introduces a conceptually unique approach, that may be useful for both diagnostics and therapeutics.